Good food served quietly. the Mime restaurants / A : - Khokle, Pradyumana, (SAGE business cases., 2020)
The case captures the origin and initial years of two restaurants, "Mirchi & Mime" and "Madeira & Mime," which exclusively employed speech and hearing impaired (SHI) persons as servers (often called "waiters" in India). The restaurants were started by two first-generation entrepreneurs through the establishment of a new company called Squaremeal Foods Private Limited (SFPL); the entrepreneurs aspired to expand the concept into a nationwide chain of restaurants employing 500 SHI persons.While the case is written primarily from the perspective of the two main founders, it also includes the views of a few employees and customers of the restaurants. It documents how the initial restaurants were set up, captures significant incidents in the initial period and discusses the effect that these incidents had on the working of the restaurants. Further, it describes the challenges that the founders faced in the recruitment of people with speech and hearing impairment, and in the commencement of operations of one fine dining restaurant and one gastropub that were staffed, at the level of servers, exclusively by SHI persons. The two founders had no prior experience with either employing SHI persons or working in the food industry. The case narrates the reactions of and effects on the SHI persons themselves, their families, others working at these outlets and customers visiting the outlets.Finally, the case lists the recognition received by SFPL for its efforts and success, and outlines SFPL's plans for the immediate future.